Choledocholithiasis Management: Comparing Efficacy and Safety of Endoscopic Retrograde Cholangiopancreatography and Open Surgical Exploration (Asian Journal of Pharmaceutics (AJP), 2025)
Choledocholithiasis is a significant issue in gallstone disease, and common bile duct (CBD) stonescan cause serious complications. Objective: This retrospective study compared the outcomes of endoscopicretrograde cholangiopancreatography (ERCP) and laparotomic surgery for choledocholithiasis at a tertiary carefacility. Methods: Thirty-eight patients were divided into two groups: Group 1 (n = 21) underwent ERCP, whereasGroup 2 (n = 17) underwent open laparotomy with biliary drainage. Liver function tests, including bilirubin,thymol turbidity, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels, were performedbefore and after the intervention. Results: In Group 1, serum bilirubin levels decreased significantly from 172.3± 2.21 μmol/L to 24.2 ± 0.97 μmol/L postoperatively (P < 0.001), with significant improvements in the thymoltest, ALT, and AST (P < 0.05). Group 2 showed moderate, non-significant biochemical improvements. Group 1experienced no complications, whereas one patient in Group 2 had partial failure of the biliary-enteric anastomosis.Patients in Group 1 had shorter hospital stays than those in Group 2. Conclusion: The results support that ERCP isthe preferred initial treatment for CBD stones when technically feasible, leading to quicker liver recovery, fewercomplications, and reduced hospital stays. Laparotomic surgery remains crucial when ERCP fails or in cases thatare complex.